Problems and Opportunities of Girls Education (A case study in Namobudda Kavre) - Acharya, Suresh (Research Journal of Padmakanya Multiple Campus, 2024)
Education is the backbone of the society where girl education plays crucial role in the development of society as well as country .Namobuddha is a significant Buddhist pilgrimage site located in Kavre District, Nepal. The main objective of this research was to understand the perception of people regarding problems and opportunities of girl’s education in this location. Interview, method schedule questionnaire, observation method was applied to collect data from respondents. Data analysis was done through MS Excels. The development of the country is being presented with both opportunities and problems as a result of the recent major advancements in girls' education in Nepal. Giving girls access to high-quality education gives them the knowledge and skills they need to make a significant contribution to society and end the cycle of poverty. Despite the advancements, obstacles still stand in the way of girls' education in Nepal being fully realized. Boys' schooling is frequently given priority over girls' by sociocultural norms that are firmly anchored in traditional practices. Girls' access to school is still being hampered by early marriage, gender-based violence, and a lack of knowledge about the advantages of education. Girls' educational possibilities are disproportionately impacted by the poor infrastructure, scarce resources, and lack of trained teachers in remote rural locations. To overcome these obstacles and provide equal educational opportunities for everyone, the government, communities, and NGOs must work together.